MENEROPONG KONSEP QATH’I DAN ZANNI DALAM PEMIKIRAN ISLAM - Abdul Rahim (AL-Fikr, 2015)
This article discusses the concept of qath'i and Zanni in Islamic thought. The al-Nas dalalah is a hadis which has a single meaning that it is not possible to accept an interpretation such as ta'wil, takhsis and tabdil and other so-called definitive. The pronouncement Zanni is the opposite of the qath'i, both in terms of dalalah Zanni and wurud. Zanni teachings are teachings which are the elaboration of a definitive teachings (implementable). Zanni teachings that do not contain the truth itself which is the opposite of the definitive teachings that are universal, teachings Zanni bound by space, time, circumstances and conditions. Islamic teachings can apply to all areas and for all ages. The basic tenets are universal, absolute truth, remains unchanged and can not be altered by the scholars-in number only about 500, paragraph, or approximately 14% of all the verses of the Qur'an. But the details and the purpose of the implementation of the basic doctrines contained in the Koran is tailored to the circumstances of a particular place and time, so-called Islam shalih li kulli zamaan wa makaan (actual).